WS-BPEL 2.0 beginner's guide : design and develop WS-BPEL executable business processes using Oracle SOA Suite 12c - Juric, Matjaz B.; Weerasiri, Denis (Learning by doing (Packt Publishing), 2014)
If you are a software architect, a designer, a software developer, an SOA and BPM architect, a project manager, or a business process analyst who is responsible for the design and development of business processes, composite applications, and BPM/SOA solutions, then this book is for you. You should have a clear grasp of general SOA concepts including business processes and web services, but no prior knowledge of the BPEL language is required.